Global Genome Mining Reveals the Distribution of Diverse Thioamidated RiPP Biosynthesis Gene Clusters - Malit, Jessie James Limlingan; Wu, Chuanhai; Liu, Ling-Li; Qian, Pei-Yuan (Frontiers in Microbiology, 2021)
Thioamidated ribosomal peptides are recently characterized natural products belonging to the class of ribosomally synthesized and post-translationally modified peptides (RiPPs) with a wide range of potent bioactivities, such as antibiotic, antiproliferative, and cytotoxic activities. These peptides are distinguished by the presence of thioamide bonds in the peptide backbone and catalyzed by the YcaO-TfuA protein pair with its genes adjacent to each other. Genome mining has facilitated an in silico approach to identify biosynthetic gene clusters responsible for secondary metabolite production. In this work, publicly available genomic data were used to detect and illustrate the diversity of putative BGCs encoding thioamidated ribosomal peptides. AntiSMASH and RiPPER analysis identified 2,326 unique TfuA-related BGCs and 5,567 precursor peptides, even on phyla where the presence of these clusters have not been previously described. Several additional biosynthetic genes were colocalized with the detected BGCs, suggesting an array of possible chemical modifications. This study shows that thioamide peptides occupy a wide unexplored chemical landscape.